Country brand equity: a comparison between the USA and China - de Queiroz, Lívia (2015)
Objective – This article aims to identify differences between country brand equities in the USA and China.Design/methodology/approach – The research was descriptive and quantitative, using as survey method self-administered questionnaires applied to 386 Brazilian respondents who are students from a public university in the Brazilian state of São Paulo.Theoretical foundations – Marketing and brand techniques may be applied to countries, and it is even possible to improve a country’s competitive position in the global market in this way. Research about the value of country brand equities is recent and there is no consensus in literature concerning the nature of this value.Findings – We found that the USA’s country brand equity is greater than China’s; the USA presented higher averages than China in all dimensions as well as in the global value.Contributions – The results represent a contribution to studies about country brand equity, which are new and scarce. From a practical point of view, the results may be used as a source of information in projects and international marketing activities by countries that possess automotive industries; by countries that have invested or want to invest in Brazil, in its automotive industry; and by countries that export cars to Brazil.